Efficient nitrate synthesis via ambient nitrogen oxidation with Ru-doped TiO₂/RuO₂ electrocatalysts - Kuang, Min (2022)
A facile pathway of the electrocatalytic nitrogen oxidation reaction (NOR) to nitrate is proposed, and Ru-doped TiO2 /RuO2 (abbreviated as Ru/TiO2 ) as a proof-of-concept catalyst is employed accordingly. Density functional theory (DFT) calculations suggest that Ruδ + can function as the main active center for the NOR process. Remarkably doping Ru into the TiO2 lattice can induce an upshift of the d-band center of the Ru site, resulting in enhanced activity for accelerating electrochemical conversion of inert N2 to active NO*. Overdoping of Ru ions will lead to the formation of additional RuO2 on the TiO2 surface, which provides oxygen evolution reaction (OER) active sites for promoting the redox transformation of the NO* intermediate to nitrate. However, too much RuO2 in the catalyst is detrimental to both the selectivity of the NOR and the Faradaic efficiency due to the dominant OER process. Experimentally, a considerable nitrate yield rate of 161.9 µmol h-1 gcat -1 (besides, a total nitrate yield of 47.9 µg during 50 h) and a highest nitrate Faradaic efficiency of 26.1% are achieved by the Ru/TiO2 catalyst (with the hybrid composition of Rux Tiy O2 and extra RuO2 by 2.79 wt% Ru addition amount) in 0.1 m Na2 SO4 electrolyte.